Youtube Videos on the Pythagorean Theorem: Didactic Analysis of the Relevance of Audiovisual Content - Esquivel-Grados, José; Basilio-Reyes, Sheyla; Martínez-Zocón, Raúl; Basilio-Lovatón, Edwar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This article presents the findings of a research study that set out to carry out a didactic analysis of the relevance of audiovisual content of YouTube videos on the Pythagorean theorem in accordance with the guidelines of current didactic theories. In the mixed-methods study, a descriptive analysis was employed for quantitative data and a discourse analysis for qualitative data. In general, the videos in question fail to demonstrate the use of conceptual elements (point, line and plane), visual elements (colour, size, texture, contrast) and relational elements in relation to space. Furthermore, the use of formal language is inadequate, with a lack of contextualised applications and cases, sources and resources for learning, and feedback. This contrasts with the attention paid to previous knowledge. The videos analysed do not present relevant audiovisual content.